Demokratisasi Dalam Politik Kepartaian Islam: (Studi Komparatif PPP di Indonesia dan PAS di Malaysia) - Ummatin, Khoiro (POROS ONIM: Jurnal Sosial Keagamaan, 2020)
This paper is the result of a literature search comparing the democracy process to two Islamic parties, the Partai Persatuan Pembangunan (PPP) in Indonesia and the Partai Islam Se-Malaysia (PAS) in Malaysia. The study confirms that although both of these Islamic parties have a similar struggle, they have a difference in the process of democratization. Similarly, both parties are always experiencing obstacles in every general election in particular regarding the public trust of both parties. PPP in Indonesia on its way has not won the elections, like PAS in Malaysia. PAS in Malaysia is the opposition party against the UMNO party based ethnic (Malay). The study suggested the importance of advanced studies to see comprehensively on the contributions and challenges of the Islamic parties in Indonesia and Malaysia so that studies have a deeper analysis base.